The effect of social media use on psychological wellbeing among students in a medical school - Lokesh, Derangula; M., Swethashree; M. R., Narayanamurthy; Gopi, Arun; Bhavana, Mungara Suma (International Journal Of Community Medicine And Public Health, 2022)
Background: These days, mobile technology plays a key role in influencing the impact of social media and screen time. The sheer number of hours spent on social media and how potentially harmful it is for students’ psychological well-being; little research has been done on the subject. The research aims at finding out how social media use impacts the mental health of medical college students. Methods: A cross-sectional study was conducted involving 553 students from January to June 2021 using purposive sampling. Rescue time mobile applications, SNSQ, and PWB scale were used to collect data. The average screen time was measured in minutes, and descriptive statistics were analyzed. A p=0.05 was considered statistically significant. Results: A total of 553 medical students participated in this study. There were 547 (98.6%) students use smartphones, the average internet cost was 282.5±167.1 rupees Maximum number of study participants is fond of using WhatsApp at regular intervals in a day 3.17±SD (0.9), followed by Instagram 2.45±SD (1.2). Social media usage screen time in minutes was observed for a week and it was found that around 123 participants (22%) spent more time, i.e., >3000 minutes, which is severe according to Munnaji et al. Conclusions: Our research showed that screen time almost always exceeded the permissible limit, but it had little effect on psychological well-being. Managing excessive screen time is important. Limiting it is ideal. Parents and students need to be educated and restricted from using screens and social media.